A workflow of massive identification and application of intron markers using snakes as a model. Issue 23 (22nd October 2017) - Li, Jiang‐Ni; He, Chong; Guo, Peng; Zhang, Peng; Liang, Dan
Abstract: Relative to the commonly used mitochondrial and nuclear protein‐coding genes, the noncoding intron sequences are a promising source of informative markers that have the potential to resolve difficult phylogenetic nodes such as rapid radiations and recent divergences. Yet many issues exist in the use of intron markers, which prevent their extensive application as conventional markers. We used the diverse group of snakes as an example to try paving the way for massive identification and application of intron markers. We performed a series of bioinformatics screenings which identified appropriate introns between single‐copy and conserved exons from two snake genomes, adding particular constraints on sequence length variability and sequence variability. A total of 1, 273 candidate intron loci were retrieved. Primers for nested polymerase chain reaction (PCR) were designed for over a hundred candidates and tested in 16 snake representatives. 96 intron markers were developed that could be amplified across a broad range of snake taxa with high PCR successful rates. The markers were then applied to 49 snake samples. The large number of amplicons was subjected to next‐generation sequencing (NGS). An analytic strategy was developed to accurately recover the amplicon sequences, and approximately, 76% of the marker sequences were recovered. The average p ‐distances of the intron markers at interfamily, intergenus, interspecies, and intraspecies levels were .168, .052, .015, and .004, respectively, suggesting that they were useful to study snake relationships of different evolutionary depths. A snake phylogeny was constructed with the intron markers, which produced concordant results with robust support at both interfamily and intragenus levels. The intron markers provide a convenient way to explore the signals in the noncoding regions to address the controversies on the snake tree. Our improved strategy of genome screening is effective and can be applied to other animal groups. NGS coupled with appropriate sequence processing can greatly facilitate the extensive application of molecular markers. Abstract : In this study, we performed a genome‐wide survey and identified 1, 273 intron loci as potential phylogenetic markers for snakes, which provide a valuable data resource to the snake evolutionary research community. From this candidate pool, 96 novel intron markers were developed that had high PCR successful rates across a wide taxonomic range. The markers were then applied to a real case, which demonstrated that they were useful in resolving both deep and shallow‐level divergences of snakes.